ОСОБЛИВОСТІ Я-КОНЦЕПЦІЇ У ОСІБ З РІЗНИМИ РІВНЯМИ АКТУАЛЬНОЇ ТА ОСОБИСТІСНОЇ ТРИВОЖНОСТІ - Анна Вовк (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the vital topic of mutual influence of state and trait anxiety and peculiarities of I-conception: self-attitude, self-monitoring and self-presentation.Persons with high level of state anxiety also have higher level of self-monitoring, self-confidence, self-management and intrinsic value. Persons with high level of trait anxiety have higher level of self-handicapping, ingratiation, supplication and self-attachment. State anxiety has positive correlation with self-confidence and intrinsic value. Trait anxiety has positive correlation with self-confidence, self- attachment and internal conflict. State anxiety is connected directly with positive characteristics of I-conception and trait anxiety has ambivalent connections with I-conception characteristics.Factor model shows connection between trait anxiety, internal conflict, self- handicapping and self-blaming and between state anxiety and self-confidence and makes clear adaptive role of medium state anxiety and neurotic character of trait anxiety.